Growth and Flower Yield of Tagetus patula Plants on Tannery Waste Amended Soil Medium - V.K. Shukla2, S. Singh2*, P.K. Singh1, V. Kumar1 and (Recent Research in Science and Technology, 2011)
Aim of the present study was to evaluate the effect of tannery waste on growth and flower yield of Tagetus patula. The planting media were prepared by mixing garden soil, sand and tannery waste in the ratio of 3:3:1, 3:3:2, 3:3:3, 3:3:4 and 3:3:5. The flower yield data obtained showed an increase in number (90 %) and weight (59 %) of flowers in Tagetus patula planted in medium with ratio of 3:3:2. Increase in plant height, shoot dry weight, root dry weight and numbers of branches were recorded maximum when plants were grown in planting medium with ratio of 3:3:1. However, a decrease in growth and flower yield of Tagetus patula was found when it was planted in media (higher tannery waste) containing garden soil: sand: tannery waste in the ratio of 3:3:3, 3:3:4 and 3:3:5. The results of the present study clearly showed that tannery waste at lower concentration promotes vegetative growth and flower yield of Tagetus patula and behaves as growth inhibitor at higher concentrations. Therefore, tannery waste can be successfully utilized in planting medium for production of Tagetus patula flowers. There is also a need to screen the effect of tannery waste based planting medium on other non edible floricultural crops.